Hukum jual beli valuta asing: Pengertian dan problematika jual beli valuta asing dalam perspektif hukum Islam - Amelia, Novita Dwi (Maliki Interdisciplinary Journal, 2024)
When carrying out buying and selling activities with parties from foreign countries, there are several obstacles that occur, one of which is related to different currencies. Because international buying and selling must use the agreed currency. This means that the parties are obliged to use foreign currency or what is usually called foreign currency. This gives rise to al-sharf activities or buying and selling foreign currency. Therefore, here the author will try to explain the meaning related to buying and selling foreign exchange from an Islamic legal perspective.